A novel tissue culture model for evaluating the effect of aging on stem cell fate in adult microvascular networks - Mohammad S. Azimi; Jessica M. Motherwell; Maria Dutreil; Ryan L. Fishel; Matthew Nice; Nicholas A. Hodges; Bruce A. Bunnell; Adam Katz; Walter L. Murfee (GeroScience, 2020)

Correction to: Microbial Exchange via Fomites and Implications for Human Health - Brent Stephens; Parham Azimi; Megan S. Thoemmes; Mohammad Heidarinejad; Joseph G. Allen; Jack A. Gilbert (Current Pollution Reports, 2019)
The article Microbial Exchange via Fomites and Implications for Human Health, written by Brent Stephens, Parham Azimi, Megan S. Thoemmes, Mohammad Heidarinejad, Joseph G. Allen, and Jack A. Gilbert, was originally published electronically on the publisher’s internet portal

Microbial Exchange via Fomites and Implications for Human Health - Brent Stephens; Parham Azimi; Megan S. Thoemmes; Mohammad Heidarinejad; Joseph G. Allen; Jack A. Gilbert (Current Pollution Reports, 2019)

Analysis of drought recurrence conditions using first-order reliability method - S. Azimi; M. Azhdary Moghaddam; S. A. Hashemi Monfared (International Journal of Environmental Science and Technology, 2019)

Simultaneous sulfamethoxazole and trimethoprim removal and biofilm growth characteristics in attached growth bioreactor - N. Azimi; G. D. Najafpour; A. H. Hassani; S. M. Borghei (International Journal of Environmental Science and Technology, 2018)

Artificial neural network coupled with wavelet transform for estimating snow water equivalent using passive microwave data - A B Dariane; S Azimi; A Zakerinejad (Journal of Earth System Science, 2014)